2020
DOI: 10.3390/cancers12123729
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Acquired Resistance to Immunotherapy in Lung Cancer: Unveiling the Mechanisms Underlying of Immune Checkpoint Blockade Therapy

Abstract: After several decades without maintained responses or long-term survival of patients with lung cancer, novel therapies have emerged as a hopeful milestone in this research field. The appearance of immunotherapy, especially immune checkpoint inhibitors, has improved both the overall survival and quality of life of patients, many of whom are diagnosed late when classical treatments are ineffective. Despite these unprecedented results, a high percentage of patients do not respond initially to treatment or relapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 172 publications
0
55
0
Order By: Relevance
“…Furthermore, resistance to immunotherapy in lung cancer manifests as a lack of initial response or clinical benefit to therapy (primary resistance) or tumor progression after the initial period of response (acquired resistance). The primary resistance prevents the infiltration or function of immune cells in the TME, while Loss of T cell function may be a potential mechanism for acquired resistance to immunodetection point inhibitors ( 18 , 19 ). In addition, metabolic properties of non-small-cell lung cancers can reprogram stromal cells to induce resistance to EGFR inhibitors ( 11 , 20 ).…”
Section: Different Mechanisms Of Chemotherapy Resistance In Nsclcmentioning
confidence: 99%
“…Furthermore, resistance to immunotherapy in lung cancer manifests as a lack of initial response or clinical benefit to therapy (primary resistance) or tumor progression after the initial period of response (acquired resistance). The primary resistance prevents the infiltration or function of immune cells in the TME, while Loss of T cell function may be a potential mechanism for acquired resistance to immunodetection point inhibitors ( 18 , 19 ). In addition, metabolic properties of non-small-cell lung cancers can reprogram stromal cells to induce resistance to EGFR inhibitors ( 11 , 20 ).…”
Section: Different Mechanisms Of Chemotherapy Resistance In Nsclcmentioning
confidence: 99%
“…Computational Analysis of REsistance (CARE) is a computational method focused on targeted therapies, to infer genome-wide transcriptomic signatures of drug efficacy from cell line compound screens ( Jiang et al, 2018 ). Previous studies have confirmed that the efficacy of immunotherapy is strongly influenced by the composition and abundance of immune cells in the TME ( Boyero et al, 2020 ).…”
Section: Introductionmentioning
confidence: 77%
“…Mechanistically, anti-PD-1 immunotherapy acts by breaking the interaction between PD-1 and PD-L1, which are responsible for the promotion of cancer immune evasion [23]. However, the application of anti-PD-1 immunotherapy in LUAD is limited by the primary or acquired drug resistance [23,24]. Recently, circRNAs have been reported to play vital roles in the tumorigenesis and progression of tumors [25,26].…”
Section: Discussionmentioning
confidence: 99%